Desktop conferencing using ISDN card : Part I : data communication [microfilm] - 451695 Pun, Chee Kent (Kuala Lumpur : UTM, 1993)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1993